2015
DOI: 10.1371/journal.pone.0130713
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae Modulates Immunity by Polarizing Human Macrophages to a M2 Profile

Abstract: Current data suggest that Neisseria gonorrhoeae is able to suppress the protective immune response at different levels, such as B and T lymphocytes and antigen-presenting cells. The present report is focused on gonococcus evasion mechanism on macrophages (MФ) and its impact in the subsequent immune response. In response to various signals MФ may undergo classical-M1 (M1-MФ) or alternative-M2 (M2-MФ) activation. Until now there are no reports of the gonococcus effects on human MФ polarization. We assessed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…8), we postulate that M2 macrophages may be the more relevant phenotype within the genital tract. Escobar et al (2013) had previously suggested that cytokines induced by N. gonorrhoeae from RAW 264.7 mouse macrophages correspond to an M2 profile and had recently published that N. gonorrhoeae can polarize Survival, apoptosis and cytokine modulation by Neisseria gonorrhoeae in human macrophages 555 human macrophages to an M2 profile (Ortiz et al, 2015). The phenotype of macrophages in the genital tract of patients will have to be investigated to determine whether there is polarization during natural gonococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…8), we postulate that M2 macrophages may be the more relevant phenotype within the genital tract. Escobar et al (2013) had previously suggested that cytokines induced by N. gonorrhoeae from RAW 264.7 mouse macrophages correspond to an M2 profile and had recently published that N. gonorrhoeae can polarize Survival, apoptosis and cytokine modulation by Neisseria gonorrhoeae in human macrophages 555 human macrophages to an M2 profile (Ortiz et al, 2015). The phenotype of macrophages in the genital tract of patients will have to be investigated to determine whether there is polarization during natural gonococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…In activated macrophages, M1 and M2b are the main cell types expressing and secreting TNF‐α . Accumulating evidences have shown that TNF‐α, in combination with other markers, such as IL‐10, LIGHT, CCL1, or/and IL‐6, can discriminate M2b from the other subtypes of macrophages very well . In addition, TNF‐α is considered a marker of M2b macrophages in many review articles …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…IL‐6 is highly expressed in M1 and M2b macrophages but not in M2a and M2c . Growing data show that in combination with other markers (IL‐10, LIGHT, CCL1, or/and TNF‐α), IL‐6 can identify M2b from the other macrophage subsets …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 2 more Smart Citations